MEDIATORS OR MAGICIANS? THE MEDIATOR’S PSYCHOLOGICAL CRAFT IN MIRACULOUSLY RESOLVING MOST COMPLEX LEGAL DISPUTES AMICABLY - Mishra, Ashutosh; Shukla, Shruti (ShodhKosh: Journal of Visual and Performing Arts, 2022)
There are so many cases in Indian Judiciary for which after a period of time, even the litigants give up the hope of them being resolved. But when the same cases get referred to Mediation, it has been witnessed that quite often they end up not just settling amicably but the parties at disputes also come back together. When the conflict is same, the parties in the conflict are same then what does actually change is the process and approach that was used to solve the dispute. Mediation is the ship that travels at the will and self-determination of the parties and the reaches to its shore. But like every ship needs a captain for it to travel in the both, the peaceful oceans and the cross through the fierce storm, Mediation also is impossible without a skillful Mediator who plays the role of the captain in this process. The Mediator uses his skill to help the parties get a clear vision through the storm of their dispute and helps them analyze how deep they are in waters. What are the chances of their survival if they travel solo and what if they come together. The Mediator helps the parties realize their actual intent and whether they want to continuously keep travelling at the ocean or actually reach the shore too. For all of this self-deliberation of the parties, the Mediator has to keep an extremely balanced state of mind and emotion to actually make this happen. The Mediator has to be very cautious about the length and breadth of his role and the extent to which he gets involved. This paper discusses about the soft skills and crucial role that the Mediator plays that shifts the psychology of the parties from dispute to amicable settlements even after hating and fighting with each other for years.